Fault signature analysis for medium voltage overhead line based on new characteristic indices - Asman S.H.; Ab Aziz N.F.; Abd Kadir M.Z.A.; Amirulddin U.A.U. (Institute of Electrical and Electronics Engineers Inc., 2023)
Animals; Lightning; Overhead lines; Wavelet transforms; Characteristic indices; Current parameters; Digital fault recorder; Electrical performance; Equipment failures; Geographical area; Lightning strikes; Medium voltage overhead lines; Outages